Multi-slice CT coronary angiography versus invasive coronary angiography in the assessment of graft patency after coronary artery bypasses graft surgery - Khaled M. Elmaghraby; Salwa R. Demitry; Eman A. Hasaballah; Nady A. Razik (The Egyptian Heart Journal, 2023)
Abstract Background The long-term patency of arterial and venous grafts is crucial for the success of CABG. This study was designed to investigate graft patency using 128-slice coronary computed tomography angiography (CCTA) and compared the results with those obtained using invasive coronary angiography (ICA). In this observational cross-sectional study, we included 40 symptomatic post-CABG patients underwent CCTA and ICA within the same month. Results Fifty-five percent were aged more than 60 years, and 80% were males. 67.5% had diabetes, 90% had hypertension, and 30% were smokers. Mean body mass index was 28.89 ± 5.17 kg/m2. Mean duration since CABG was 5.25 ± 4.04 years. In total, 124 native vessels and 97 grafts were assessed using CCTA and ICA. CCTA delineated 8 non-cannulated venous grafts and 6 non-cannulated left internal mammary artery grafts. CCTA required a significantly lower radiation dose (1165.77 ± 123.54 vs. 47,589.78 ± 6967.53, p < 0.001). Conclusion CCTA can be as accurate as ICA in assessing bypass grafts with less radiation dose, providing a non-invasive reliable tool for evaluation.